Leukocyte telomere length in patients with transfusion-dependent thalassemia - Nithita Nanthatanti; Adisak Tantiworawit; Pokpong Piriyakhuntorn; Thanawat Rattanathammethee; Sasinee Hantrakool; Chatree Chai-Adisaksopha; Ekarat Rattarittamrong; Lalita Norasetthada; Wirote Tuntiwechapikul; Kanda Fanhchaksai; Pimlak Charoenkwan; Sirinart Kumfu; et al. (BMC, 2020)
Abstract Background Thalassemia is a hereditary hemolytic anemia with a severity ranging from mild, non-transfusion dependent to severe chronic anemia requiring lifelong transfusion. Transfusional iron overload is a major complication in patients with transfusion-dependent thalassemia (TDT). Telomeres are sequences of nucleotides forming the end caps of chromosomes that act as a DNA repair system. Iron overload in thalassemia can cause increased oxidative stress which leads to cellular damage and senescence. This may result in telomere length shortening. The degree of telomere length shortening may reflect the severity of thalassemia. Methods This research aimed to study the leukocyte telomere length in patients with TDT in comparison to non-thalassemic individuals and to identify the clinical and laboratory parameters that are associated with telomere length. We conducted a cross-sectional study in patients with TDT aged ≥18 years. Leukocyte telomere length was measured by real-time quantitative PCR. Results Sixty-five patients with TDT were enrolled onto the study. There were 37 female patients (54.4%). The median age was 27 (18-57) years, and mean pre-transfusion hemoglobin level was 7.1 (± 1.07) g/dL. The mean telomere to single copy gene (T/S) ratios of patients with TDT and the controls were 0.72 ± 0.18 and 0.99 ± 0.25, respectively (p < 0.0001). There was a significant correlation between the T/S ratio and age (p = 0.0002), and hemoglobin level (p = 0.044). There was no correlation between telomere length and other factors. Conclusions Our study showed that TDT patients had shorter leukocyte telomere length compared with controls. Leukocyte telomere shortening in TDT was an aging-dependent process and associated with lower hemoglobin level.